The impact of family and friend support of physical activity on the participation in physical activity within Indigenous individuals in Saskatoon - Mainra, Nisha K.; Ironside, Avery K.; Johnson, Shara R.; Rolfes, Tayha T.; Fatima, Muqtasida A.; Melanson, Kendra; Foulds, Heather J. A. (Frontiers in Sports and Active Living, 2024)
Social support within Indigenous worldviews is recognized as a component of health and has been associated with physical activity and sedentary behaviour. Physical Activity (PA) is a modifiable behaviour that can help reduce risks of disease and benefit many dimensions of health. The purpose of this study was to compare the physical activity of Indigenous adults in Saskatchewan with and without family/friend support of PA. The Family Influence on Physical Activity questionnaire was used to record the extent and forms of family/friend support of PA. The Godin Shepard Leisure Exercise Questionnaire (GSLEQ) was used to measure weekly PA, including moderate PA (MPA), vigorous PA (VPA), exercise frequency (WEF) and GSLEQ scores. Indigenous participants overall, First Nations and Cree participants specifically with family/friend involvement in PA reported greater weekly WEF and GSLEQ scores. Indigenous participants overall and First Nations participants specifically with family and friends who watch them engage in PA reported greater weekly VPA and GSLEQ scores. Among First Nations and Cree participants specifically, those with family/friends encouragement of PA reported greater weekly VPA, WEF and GSLEQ scores. Furthermore, First Nations participants with active family/friends reported significantly greater weekly VPA (36.8 ± 51.5 min•week -1 vs. 80.2 ± 108.5 min•week -1 ; p=0.01). Greater weekly VPA was found in Métis participants with family/friend involvement in PA and with family/friends who watch them engage in PA (67.6 ± 59.6 min•week -1 vs. 29.5 ± 40.8 min•week -1 ; p=0.01). Social support, specifically family/friends involvement, has a significant impact on Indigenous participation in PA.